Execution of Mortgage Rights: Creditor’s Legal Remedies for Third Party Claims Against Auctioned Collateral - Putu Devi Yustisia Utami; Ni Putu Purwanti; Gusti Ayu Era Yusnia; Sally Paramitha; Made Gde Surya Dharma Palguna (Warmadewa Press, 2025)
This study examines the legal implications of lawsuits filed against collateral objects on the implementation of mortgage right execution under Indonesia Mortgage Law. Normatively, Article 6 of the Mortgage Law stipulates that upon the debtor’s default, the first-ranking mortgage holder has the right to independently sell the mortgaged object through a publich auction (parate execution). However, in practice, such executions are frequently obstructed by pre-auction lawsuits concerning the collateral, thus impeding enforcement. Using an empirical juridical method, this research analyzes the legal consequences of lawsuits on the execution of mortgage rights and the creditor’s legal remedies upon a lawsuit filed against the object of the mortgage right. The result of this study indicate that a lawsuit concerning the collateral object for auction legally prevents the execution of mortgage rights through parate execution, and the legal remedy available to banks as a creditor is to pursue execution through an executorial title in District Court. This process requires a fiat executions issued by the Chief Judge of the District Court, in accordance with Article 34 paragraph (3) of the Minister of Finance Regulation concerning Auction Guidelines 2023. This study recommend that the government should enact a specific regulation governing the procedures for executing mortgage rights via District Courts as mandated by article 26 of Mortgage Rights. Furthermore, the judiciary is encouraged to establish dedicated units within District Courts specifically tasked with handling collateral executions, to develop and implement of nationwide online filling system for execution applications.